Electric and Magnetic Fields of the High Voltage Autotransformer - Deltuva, R.; Virbalis, J. A.; Gečys, S. (Elektronika ir Elektrotechnika, 2010)
High voltage power autotransformer is one of the strongest sources of the electric and magnetic fields in the electrical power systems. The autotransformer with surroundings was modelled using finite element method for evaluate magnetic and electric fields distribution around it. The modelling results show that magnetic field near autotransformer is not dangerous for human practically. But there are zones near autotransformer and connected to it 330 kV network, where the electric field strength can exceed the maximal admissible values. Therefore the measures must be used for the electric field damping in these zones.